A new comprehensive trait database of European and Maghreb butterflies, Papilionoidea - Middleton-Welling, Joseph; Dapporto, Leonardo; García-Barros, Enrique; Wiemers, Martin; Nowicki, Piotr; Plazio, Elisa; Bonelli, Simona; Zaccagno, Michele; Šašić, Martina; Liparova, Jana; Schweiger, Oliver; Harpke, Alexander; et al. (Scientific data, 2020)
Trait-based analyses explaining the different responses of species and communities to environmental changes are increasing in frequency. European butterflies are an indicator group that responds rapidly to environmental changes with extensive citizen science contributions to documenting changes of abundance and distribution. Species traits have been used to explain long- and short-term responses to climate, land-use and vegetation changes. Studies are often characterised by limited trait sets being used, with risks that the relative roles of different traits are not fully explored. Butterfly trait information is dispersed amongst various sources and descriptions sometimes differ between sources. We have therefore drawn together multiple information sets to provide a comprehensive trait database covering 542 taxa and 25 traits described by 217 variables and sub-states of the butterflies of Europe and Maghreb (northwest Africa) which should serve for improved trait-based ecological, conservation-related, phylogeographic and evolutionary studies of this group of insects. We provide this data in two forms; the basic data and as processed continuous and multinomial data, to enhance its potential usage.
Keywords: severní Afrika; Databases, Factual; Biological Evolution; Conservation of Natural Resources; databáze faktografické; Animals; ekologie; Africa, Northern; motýli; Butterflies; zachování přírodních zdrojů; Phylogeny; zvířata; fylogeneze; biologická evoluce; Evropa; Ecology; Europe